2022
DOI: 10.3390/v14122744
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Dependent Role for nsP3 Macrodomain ADP-Ribose Binding and Hydrolase Activity during Chikungunya Virus Infection

Abstract: Chikungunya virus (CHIKV) causes outbreaks of rash, arthritis, and fever associated with neurologic complications, where astrocytes are preferentially infected. A determinant of virulence is the macrodomain (MD) of nonstructural protein 3 (nsP3), which binds and removes ADP-ribose (ADPr) from ADP-ribosylated substrates and regulates stress-granule disruption. We compared the replication of CHIKV 181/25 (WT) and MD mutants with decreased ADPr binding and hydrolase (G32S) or increased ADPr binding and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…3A). A previous study has shown that mutations in the CHIKV nsP3 MD Asp10, Gly32, Val33 Thr111, Gly112, Tyr114 and Arg144 residues impair both ADPr binding and hydrolysis activity, indicating their critical role in enzyme activity [13–15,18,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). A previous study has shown that mutations in the CHIKV nsP3 MD Asp10, Gly32, Val33 Thr111, Gly112, Tyr114 and Arg144 residues impair both ADPr binding and hydrolysis activity, indicating their critical role in enzyme activity [13–15,18,41].…”
Section: Resultsmentioning
confidence: 99%
“…Baicalin, a compound that interacts with nsP3 and demonstrates anti-CHIKV effects in cell culture, has shown promise [28]. Other small-molecule inhibitors specifically targeting CHIKV nsP3 MD including harringtonine, atovaquone, RYL 634, 6-azauridine, favipiravir and sofosbuvir have been identified but provide limited long-term relief to patients [29][30][31][32][33][34][35][36][37][38][39][40][41]. Given the lack of specific and effective inhibitors, the present study aimed to identify a potent inhibitor capable of halting viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…The study compared the replication kinetics of the wild-type CHIKV with that of CHIKV containing a mutant MD site. This mutation led to either decreased ADPr binding and hydrolase activity (G32S) or increased ADPr binding with decreased hydrolase activity (Y114A) [ 15 ]. Finally, the ultrastructural morphology and mechanical properties of CHIKV were examined using atomic force microscopy and Raman spectroscopy.…”
mentioning
confidence: 99%